Beyond the Confines of Achievement in Secondary School Biology: Higher-order thinking in Focus - Lameed, Soladoye Nurudeen; Adam, Umar Ayotunde; Ayodele, Benjamin Benson; Muraina, Ismail Olaniyi (FKIP - Universitas Riau, 2023)
Thinking at a rate higher than memorizing ideas or recalling verbatim what was learned in the previous lessons is a challenging task in teaching and learning biological concepts. Past studies have established many strategies to address this, but they are not directly linked to the ultimate solution to the problem. This study investigates the potency of problem-solving strategy to enhance student’s ability in higher-order thinking tasks in biology. A total of 118 senior secondary two biology students in their intact group participated in the study. The study employed a quasi-experimental group design. Data on higher-order thinking tasks were collected using 20 multiple-choice items titled Achievement Test in Higher-order Thinking Tasks (ATHOTT). Mean and standard deviation depicted in bar charts provide answers to the three research questions, while analysis of covariance was employed to test the hypotheses. The results revealed that problem-solving strategy enhanced students’ response to higher-order thinking tasks, male and female students did not differ in response to higher-order thinking tasks, and gender did not mediate with the problem-solving strategy to enhance students’ response to higher-order thinking tasks in biology. Teachers are, therefore, implored to engage students in problem-solving activities.